Design, sssembly, and biological evaluation of protein nanoparticles as theranostic agents and for photodynamic therapy - Al-Ani, Ali Waleed Numan (2017)
Nanoparticles derived from proteins offer a smart material for the design of a new generation of anticancer therapies. In this thesis we describe a variety of novel photodynamic therapy (PDT), drug delivery, and imaging agents that have been combined to produce theranostic systems.